2018
DOI: 10.3390/genes9060308
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Red Fox Chromosomal Fragments from the Short-Read Genome Assembly

Abstract: The genome of a red fox (Vulpes vulpes) was recently sequenced and assembled using next-generation sequencing (NGS). The assembly is of high quality, with 94X coverage and a scaffold N50 of 11.8 Mbp, but is split into 676,878 scaffolds, some of which are likely to contain assembly errors. Fragmentation and misassembly hinder accurate gene prediction and downstream analysis such as the identification of loci under selection. Therefore, assembly of the genome into chromosome-scale fragments was an important step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Finally, reads of 30 nucleotides or longer were selected and mapped to the reference genome. In the absence of a complete fox genome assembly, [36][37][38] closely related dog genome assembly (C. familiaris 3.1 genome) was used as the reference for mapping. This reference genome was also used in previous studies comparing the PFC, BFB and pituitary gland of tame vs aggressive foxes.…”
Section: Bioinformatics Analyses Of Rna-seq Datamentioning
confidence: 99%
“…Finally, reads of 30 nucleotides or longer were selected and mapped to the reference genome. In the absence of a complete fox genome assembly, [36][37][38] closely related dog genome assembly (C. familiaris 3.1 genome) was used as the reference for mapping. This reference genome was also used in previous studies comparing the PFC, BFB and pituitary gland of tame vs aggressive foxes.…”
Section: Bioinformatics Analyses Of Rna-seq Datamentioning
confidence: 99%
“…The other 23 breaks were inside single SOAPdenovo scaffolds, with five also being broken in the SOAPdenovo + RACA assembly, while the rest were either not used (4 cases) or below the 150 Kbp resolution of the SOAPdenovo + RACA assembly (14 cases). Although physical or genetic maps for gemsbok are not available to verify the SOAPdenovo + Chicago + RACA assembly, we previously showed that RACA produces highly accurate chromosome assemblies when compared to meiotic linkage [20] or cytogenetic physical maps [19], suggesting that the 47 PCFs of the gemsbok assembly accurately represent scaffold order and orientation on the gemsbok chromosomes. Therefore, using RACA allowed us to identify putatively chimeric scaffolds and superscaffolds, as well as to align components of chimeric scaffolds to their likely location on the gemsbok genome.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In this study, we upgraded the previously published fragmented dromedary camel genome assembly to nearly chromosome-level using a combination of in silico chromosome reconstructions, PCR-verification and supporting data from camel and alpaca physical maps. This approach has been previously applied to mammalian genomes, such as the Tibetan antelope (Kim et al, 2013) (2 n = 60), red fox (Rando et al, 2018) (2 n = 34), and avian species, including pigeon and peregrine falcon (Damas et al, 2017), and showed high consistency when compared with third-generation sequencing methodologies (Holt et al, 2018). Our approach resulted in a remarkable reduction in fragmentation of the original dromedary assembly by 25-fold, and an N50 increase 35-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Other reference-based algorithms e.g., RAGOUT (Kolmogorov et al, 2014) do not use the target assembly read-pair data to verify scaffold structures and orders, meaning that the target species-specific rearrangements could be missed from the reconstructed chromosome fragments, which could prove to be a problem in future candidate gene research, as a lower quality genome assembly will produce more false-negative and false-positive association signals, reducing the value of association studies (Goldfeder et al, 2016). Moreover, RACA has been successfully used for other genome assembly projects, including mammals [such as Tibetan antelope and red fox (Kim et al, 2013; Rando et al, 2018)] and birds [peregrine and saker falcons, ostrich, pigeon, and budgerigar (Damas et al, 2017; O’Connor et al, 2018)]. Finally, RACA assemblies could provide an independent source to prove and/or further improve assemblies produced with such methods as HiC, 10X or Dovetail Chicago.…”
Section: Introductionmentioning
confidence: 99%